SNF5 promotes cell proliferation and immune evasion in non-small cell lung cancer. Issue 5 (2nd May 2022) - Chen, Ying; Zhao, Meilian; Shen, Dongliang; Yi, Qian; Tang, Liling
ABSTRACT: Immune evasion is the process that tumor cells accelerate growth and metastasis by evading the recognition and attack of immune cells. SNF5 is one of the core subunits of SWI/SNF, which is involved in the development of a variety of malignancies. However, the functions of SNF5 in Non-Small Cell Lung Cancer (NSCLC) and the mechanism of SNF5 regulates immune evasion are still unclear. Based on this, we analyzed the expression of SNF5 and overall survival of lung cancer tissues through the cancer genome atlas (TCGA) database. Then we performed genetic gain and loss of function experiments with SNF5 using lentivirus infection and siRNA in NSCLC A549 and NCI-H1299 cells, respectively. We investigated the proliferation and immune evasion of these cells. We further explored the mechanism of SNF5 on NSCLC cells immune evasion. Our data showed that SNF5 was significantly increased in lung cancer tissues than that in normal lung tissues. Furthermore, SNF5 promoted NSCLC cells proliferation and the expressions of immune evasion-related genes. Meantime, overexpressed SNF5 reduced mortality of A549 cells when co-cultured with T cells. Moreover, SNF5 regulated the immune evasion by activating the signal transducer and activator of transcription (STAT3)/ phospho-STAT3 pathway in NSCLC cells. Together, our results validate SNF5 as a tumor oncogene and provide a new target for NSCLC treatment. GRAPHICAL ABSTRACT: uf0001